Influence of the supramolecular architecture on the magnetic properties of a DyIII single-molecule magnet: an ab initio investigation - Jung, Julie; Cador, Olivier; Bernot, Kevin; Pointillart, Fabrice; Luzon, Javier; Le Guennic, Boris (Beilstein Journal of Nanotechnology, 2014)
Single-crystal angular-resolved magnetometry and wavefunction-based calculations have been used to reconsider the magnetic properties of a recently reported DyIII-based single-molecule magnet, namely [Dy(hfac)3(L1)] with hfac− = 1,1,1,5,5,5-hexafluoroacetylacetonate and L1 = 2-(4,5-bis(propylthio)-1,3-dithiol-2-ylidene)-6-(pyridin-2-yl)-5H-[1,3]dithiolo[4',5':4,5]benzo[1,2-d]imidazole. The magnetic susceptibility and magnetization at low temperature are found to be strongly influenced by supramolecular interactions. Moreover, taking into account the hydrogen-bond networks in the calculations allows to explain the orientation of the magnetic axes. This strongly suggests that hydrogen bonds play an important role in the modulation of the electrostatic environment around the DyIII center that governs the nature of its magnetic ground-state and the orientation of its anisotropy axes. We thus show here that SMM properties that rely on supramolecular organization may not be transferable into single-molecule devices.
Keywords: ab initio calculations; dysprosium; magnetic properties; single-molecule magnets; supramolecular effects